Role of ion mass on damage accumulation during ion implantation in Ge. Issue 1 (29th November 2013) - Napolitani, E.; Bruno, E.; Bisognin, G.; Mastromatteo, M.; De Salvador, D.; Scapellato, G. G.; Boninelli, S.; Priolo, F.; Privitera, V.; Carnera, A.
<x xml:space="preserve">Abstract</x> The effects of sub‐amorphizing ion implantation on damage accumulation and point defect migration in Ge are investigated. We implanted ions with different masses in a Ge sample with embedded B doped deltas grown by molecular beam epitaxy, as markers for self‐interstitial generation and migration. Implant fluences and energies were selected to generate similar depth profiles of the energy density released in nuclear collisions. We show that the accumulated damage decreases by decreasing the ion mass. This is associated with an increase of effective displacement energy in dilute cascade due to point defect migration and annihilation. The change of the effective displacement energy as a function of mass has been described and satisfactorily fitted together with data from the literature. We observed that B radiation enhanced diffusion increases by decreasing the ion mass, further supporting the above view, and indicates that the migration of self‐interstitials has a role in the defect annihilation process during ion implantation in Ge. H deviates from the above scenario suggesting that damage stabilization occurs through the interaction of H with vacancies.